“The freedom within imprisonment”: lyrical self of V. Stus’s poetry as an element to reconsider traumatic experience - Тарануха, Єлизавета Валеріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
Based on the poetry of V. Stus, the article indicates the connection between the model of lyrical self and rethinking of traumatic experience. It is a part of a longtime Ph.D. comparative literature research upon the models of lyrical self in poetry of Ukrainian, Canadian, and Ukrainian-Canadian authors of 20th century: V. Stus, M. Atwood, and O. Zuyevs’kyi. Lyrical self is interpreted from H. Gadamer’s perspective of hermeneutics. The author states that the model of lyrical self and elements of style depend on traumatic experience of the poet. According to M. Travis’s classification of lyrics, poetry of V. Stus is self-display lyrics, based on the concepts related to freedom, alive-death, and dead-life. The phenomenon of freethinking in the poetry is analyzed from the perspective of personal self-assertion under the conditions of imprisonment. The lyrical self in V. Stus’ poetry is posited as one of the tools to survive traumatic experience. The article discovers that the lyrical self is constructed as a result of personal choice, self-searching, and self-building. Being imprisoned, V. Stus gains the inner freedom through freedom of thought; he establishes the identity of lyrical self as a subject of lyrics which is open for co-understanding and dialogue with society.